2011
DOI: 10.4103/2045-8932.93546
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Right Ventricular Hypertrophy using ECG Criteria in Patients with Pulmonary Hypertension: A Comparison with Cardiac MRI

Abstract: In patients with pulmonary arterial hypertension (PAH), right ventricular mass (RVM) correlates linearly with pulmonary artery pressure, and decreases with successful treatment. Accurate measurement of RVM currently requires cardiovascular magnetic resonance (CMR) imaging. We therefore tested the relationship between RVM and a simple, 12 lead ECG-derived value, the Butler-Leggett (BL) score. This has previously been validated in patients with RV hypertrophy (RVH) due to mitral stenosis. We also tested the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…CMRI is superior to radionuclide imaging because it does not require ionizing radiation and superior to electrocardiography because it is more sensitive. 39 There is also some evidence to suggest that N-terminal B-type natriuretic peptide measurements reflect changes in CMRI-determined RV structure and function in patients with PH, 33,39 but the potential of this noninvasive marker as a surrogate for outcome remains to be demonstrated. 40 The study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…CMRI is superior to radionuclide imaging because it does not require ionizing radiation and superior to electrocardiography because it is more sensitive. 39 There is also some evidence to suggest that N-terminal B-type natriuretic peptide measurements reflect changes in CMRI-determined RV structure and function in patients with PH, 33,39 but the potential of this noninvasive marker as a surrogate for outcome remains to be demonstrated. 40 The study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…59 Uniformly, in much smaller groups of patients (ranging from n=23 to n=38) than our study, various criteria for RVH have been examined, including the AHA recommended criteria. Similar to prior published work, these studies were in patients with known RVH 56–58 or, based on clinical risk factors, were at high risk for pulmonary hypertension. 59 Investigators found low sensitivity and insufficient specificity to be clearly useful in identifying RVH.…”
Section: Discussionmentioning
confidence: 53%
“…16 A more recent study compared this same criterion to the gold standard of cMRI in 28 patients known pulmonary arterial hypertension and confirmed high specificity but with similarly low sensitivities of 64–71%, depending on the definition of RVH used. 56 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown previously that isolated right ventricular pressure overload, due to pulmonary hypertension, alters the balance of QRS forces and causes right axis deviation. 7 With only the right ventricular volume overload produced by the so-called "ostium secundum" atrial septal defect, however, there is well-documented absence of right axis deviation. 8,9 Only the patients with defects permitting ventricular shunting, therefore, would be expected to have the increase in right ventricular wall tension that would affect its ventricular gradient sufficiently to alter both its depolarisation and repolarisation.…”
mentioning
confidence: 99%